2016
DOI: 10.1097/md.0000000000003077
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Trachomatis Infection-Associated Risk of Cervical Cancer

Abstract: As whether Chlamydia trachomatis infection increases the risk of cervical cancer is controversial in the literature, we performed a meta-analysis.Based on a comprehensive search of publications in the Medline, Cochrane, and EMBASE databases, we identified and extracted data from all relevant articles examining C. trachomatis infection and the risk of cervical cancer. The quality of each included study was assessed according to the 9-star Newcastle–Ottawa scale. The strength of association between the C. tracho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
123
3
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(151 citation statements)
references
References 50 publications
4
123
3
10
Order By: Relevance
“…CdtA and CdtC ensure the uptake and cellular delivery of CdtB, which harbours the catalytic activity of CDT and causes double-strand DNA breaks (DSBs) in host cells. After host cell binding and internalization by Salmonella Typhi Bacterium Gallbladder carcinoma [13] Salmonella Enteritidis Bacterium Colon carcinoma in the ascending and transverse parts of the colon [14] Chlamydia trachomatis Bacterium Carcinoma of the cervix and ovaries [104,105] particularly sensitive to these toxins. As a result, this toxin can locally eliminate immune cells, providing an obvious advantage for the bacteria.…”
Section: Bacterial Toxin-mediated Host Cell Transformationmentioning
confidence: 99%
“…CdtA and CdtC ensure the uptake and cellular delivery of CdtB, which harbours the catalytic activity of CDT and causes double-strand DNA breaks (DSBs) in host cells. After host cell binding and internalization by Salmonella Typhi Bacterium Gallbladder carcinoma [13] Salmonella Enteritidis Bacterium Colon carcinoma in the ascending and transverse parts of the colon [14] Chlamydia trachomatis Bacterium Carcinoma of the cervix and ovaries [104,105] particularly sensitive to these toxins. As a result, this toxin can locally eliminate immune cells, providing an obvious advantage for the bacteria.…”
Section: Bacterial Toxin-mediated Host Cell Transformationmentioning
confidence: 99%
“…12 The direct implication of C. trachomatis in the pathogenesis of malignancy has been highlighted in recent studies on women. It has been reported that C. trachomatis promotes HPV persistence, [13][14][15] suggesting that it should not be simply considered as a comorbidity of HPV infection, but should be regarded as an independent predictor of cervical cancer risk. Moreover, in young asymptomatic women the presence of C. trachomatis seems to significantly increase the risk of pre-cancer lesions.…”
mentioning
confidence: 99%
“…The intense interest in bacteria that induce DSBs in the host is driven largely by connections with carcinogenesis caused by enhanced genome instability. Helicobacter pylori infection is associated with stomach cancers (Hanada & Graham, ); Salmonella typhi is associated with gallbladder cancers (Koshiol et al., ); and Chlamydia trachomatis is associated with cervical cancers (Zhu, Shen, Luo, Zhang, & Zhu, ). Interestingly, all of these bacteria can introduce DSBs in host cells (Chumduri, Gurumurthy, Zadora, Mi, & Meyer, ; Grasso & Frisan, ; Hanada et al., ).…”
Section: Introductionmentioning
confidence: 99%